Technical assistance services of the International Monetary Fund - International Monetary Fund (Washington, D. C. International Monetary Fund, 1979)
This pamphlet deals with a lesser-known aspect of the Fund's work- the technical assistance provided by the Fund to its members.
"Appendix. International Monetary Fund. Chart of organization"
aia 28/09/16
Loans
Keywords: International Monetary Fund; Technical assistance; Banks and banking, central